Prevalence of ideal cardiovascular health and its relationship with relative handgrip strength in rural northeast China - Shao, Jingan; Yao, Bin; Yu, Zhecong; Xu, Jiahui; Wu, Jing; Ma, Yanan; Zheng, Liqiang; Sun, Zhaoqing (Frontiers in Cardiovascular Medicine, 2023)
Objectives We aimed to investigate ideal cardiovascular health (CVH), its relationship with handgrip strength, and its components in rural China. Methods We conducted a cross-sectional study of 3,203 rural Chinese individuals aged ≥35 years in Liaoning Province, China. Of these, 2,088 participants completed the follow-up survey. Handgrip strength was estimated using a handheld dynamometer and was normalized to body mass. Ideal CVH was assessed using seven health indicators (smoking, body mass index, physical activity, diet, cholesterol, blood pressure, and glucose). Binary logistic regression analyses were performed to assess the correlation between handgrip strength and ideal CVH. Results Women had a higher rate of ideal cardiovascular health (CVH) than men (15.7% vs. 6.8%, P < 0.001). Higher handgrip strength correlated with a higher proportion of ideal CVH (P for trend <0.001). After adjusting for confounding factors, the odds ratios (95% confidence interval) of ideal CVH across increasing handgrip strength tripartite were 1.00 (reference), 2.368 (1.773, 3.164), and 3.642 (2.605, 5.093) in the cross-sectional study and 1.00 (reference), 2.088 (1.074, 4.060), and 3.804 (1.829, 7.913) in the follow-up study (all P < 0.05). Conclusion In rural China, the ideal CVH rate was low, and positively correlated with handgrip strength. Grip strength can be a rough predictor of ideal CVH and can be used to provide guidelines for improving CVH in rural China.